2021
DOI: 10.5194/tc-15-1881-2021
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: New radar constraints support presence of ice older than 1.5 Myr at Little Dome C

Abstract: Abstract. The area near Dome C, East Antarctica, is thought to be one of the most promising targets for recovering a continuous ice-core record spanning more than a million years. The European Beyond EPICA consortium has selected Little Dome C (LDC), an area ∼ 35 km southeast of Concordia Station, to attempt to recover such a record. Here, we present the results of the final ice-penetrating radar survey used to refine the exact drill site. These data were acquired during the 2019–2020 austral summer using a ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 20 publications
5
69
0
Order By: Relevance
“…Even though such vertically long antennae would have difficulty in mounting on ground-based platforms, they provide an important opportunity for improving conventional radar systems. Modern radar sounders with phase analysis and SAR processing (e.g., Rodriguez-Morales et al, 2020;Lilien et al, 2021) are able to remove hyperbolic effects. For improving the accuracy of bedrock topography measurements, we can apply radar with high-gain and high-directivity antennae, state-of-the-art modern radar with focused SAR processing, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though such vertically long antennae would have difficulty in mounting on ground-based platforms, they provide an important opportunity for improving conventional radar systems. Modern radar sounders with phase analysis and SAR processing (e.g., Rodriguez-Morales et al, 2020;Lilien et al, 2021) are able to remove hyperbolic effects. For improving the accuracy of bedrock topography measurements, we can apply radar with high-gain and high-directivity antennae, state-of-the-art modern radar with focused SAR processing, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Ice radar observations have been conducted in the vicinity of the domes in the EAIS, such as Dome A (e.g., Sun et al, 2009;Bell et al, 2011), Dome C (e.g., Young et al, 2017;Lilien et al, 2021), and Titan Dome (Beem et al, 2021), which numerical modelling studies have identified as candidate areas for future deep drilling. In the Dome Fuji region, a candidate area for deep drilling, after ground-based radar surveys were conducted by the JARE from the late 1980s until 2013, an extensive airborne radar survey was carried out over a 20000 km 2 area during the 2014-2015 and 2016-2017 austral summers (Karlsson et al, 2018) (Fig.…”
mentioning
confidence: 99%
“…The LDC area was first highlighted as a key Beyond EPICA -Oldest Ice target site in the Van Liefferinge and study. The ice core drilling site has since then been narrowed down to a precise location on LDC through successive radar survey collections (Young et al, 2017;Lilien et al, 2021) and modeling efforts (Parrenin et al, 2017;Cavitte et al, 2018;Van Liefferinge et al, 2018;Passalacqua et al, 2018), in preparation for drilling (Fig. 1).…”
Section: The Dome C Plateau Regionmentioning
confidence: 99%
“…Depth uncertainties are also assigned to the undated IRHs (Table 4). Since these IRHs do not reach the MCM/JKB1a/EDMC01a transect, their depths are measured at the closest point along the DELORES radar transect HRB7-HRB8 to the final chosen BE-OI drill site BELDC (75.29917 • S, 122.44516 • E) (Lilien et al, 2021), and their uncertainties are constrained as described above but with their range precision defined by their SNR along this DE-LORES transect. We assume that the firn correction and error calculated at the EDC site are also applicable to this site over LDC.…”
Section: Age Attributionmentioning
confidence: 99%
“…Ice radar observations have been conducted in the vicinity of the domes in the EAIS, such as Dome A (e.g., Sun et al, 2009;Bell et al, 2011), Dome C (e.g., Young et al, 2017;Lilien et al, 2021), and Titan Dome (Beem et al, 2021), which numerical modelling studies have identified as candidate areas for future deep drilling. In the Dome Fuji region, a candidate area for deep drilling, after ground-based radar surveys were conducted by the JARE from the late 1980s until 2013, an extensive airborne radar survey was carried out over a 20000 km 2 area during the 2014-2015 and 2016-2017 austral summers (Karlsson et al, 2018) (Fig.…”
Section: Introductionmentioning
confidence: 99%